INVESTIGATING THE EFFECTIVENESS OF AI CHATBOTS IN ENHANCING SPEAKING FLUENCY AND CONFIDENCE AMONG INTERMEDIATE-LEVEL EFL LEARNERS. - Barno Qodirova (PEDAGOGS, 2024)
This study examines how intermediate-level English as a Foreign Language (EFL) learners' speaking fluency and confidence are affected by AI chatbots. This study attempts to ascertain how well AI-driven chatbots can enhance language learners' speaking abilities and confidence by including them into the learning process. Using a mixed-methods approach, the study measures speaking fluency quantitatively and learner confidence qualitatively through surveys. According to research, AI chatbots greatly improve speaking confidence and fluency, providing language teachers with useful resources.